Rhodium-Catalyzed N-Reverse Prenylation of Nonactivated Indoles - Sun, Minghe; Wei, Linsheng; Li, Changkun (Synlett, 2023)
The N-reverse prenylated indole motif is an important structure in natural products and biologically active molecules. Nevertheless, the direct N-reverse prenylation of nonactivated indoles is challenging. We report a rhodium-catalyzed regioselective N-reverse prenylation of indoles bearing various functional groups under neutral conditions. The triphenyl phosphite ligand and acetonitrile solvent together play a key role in the reactivity and selectivity.
Keywords: indoles; reverse prenylation; rhodium catalysis; allylic substitution; regioselectivity